FEATURES OF FOLLICULOGENESIS IN WOMEN WITH ENDOCRINE INFERTILITY - Anvarova, Sh.A.; Ismoilova, Sh.I.; Shukurov, F.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Endocrine infertility is defined as a woman’s inability to conceive within one year of regular unprotected sexual intercourse, primarily caused by endocrine system disorders. Aim. To study the characteristics of folliculogenesis in women with infertility caused by various endocrine pathologies and to develop more effective diagnostic and treatment methods. Materials and methods. The study included 90 women with endocrine infertility, divided into three groups: Group I – hypothyroidism (n=30), Group II – hyperprolactinemia (n=30), Group III – hyperandrogenism (n=30). A control group comprised 30 healthy women. Hormonal analysis and transvaginal ultrasound were conducted to assess the number and size of antral follicles. Statistical analysis was performed using the t-test and one-way ANOVA. Results. The mean number of antral follicles in women with endocrine infertility was significantly lower compared to the control group: for women with hypothyroidism – 4.5±1.2, with hyperprolactinemia – 5.1±1.3, and with hyperandrogenism – 6.8±1.4 (p < 0.05). The average follicle diameter was also smaller: for women with hypothyroidism – 6.2±0.8 mm, with hyperprolactinemia – 6.7± 0.9 mm, and with hyperandrogenism – 7.5±1.1 mm (p<0.05). Hormonal studies revealed significant differences in the levels of LH, FSH, prolactin, estradiol, progesterone, testosterone, T3, T4, and TSH between the study groups and the control group. Conclusion. Endocrine disorders play a key role in disrupting folliculogenesis and can lead to infertility. A differentiated approach to the diagnosis and treatment of endocrine infertility, taking into account the specific hormonal profiles of each patient, may increase the effectiveness of therapy and improve reproductive outcomes for women. Future studies should include larger and more diverse samples to confirm these findings.